Efficacy of newer insecticide formulation against white grub, Holotrichia consanguinea in groundnut (Arachis hypogaea) - BAJYA, D R; BAHETI, H S; RAZA, S K (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during kharif 2011 and 2012 at research farm of Institute of Pesticide Formulation Technology, Gurgaon (Haryana) to evaluate the bioefficacy of new insecticide imidacloprid (0.3 G) @ four differential doses, viz 10, 15, 20 and 40 kg/ha along with standard check, phorate (10G) @ 25 kg/ha and imidacloprid (200SL) @ 500 ml/ha against Holotrichia consanguinea Blanch in groundnut crop. All doses of insecticides were used as soil application in groundnut (Arachis hypogaea L.). Imidacloprid (0.3 G) @ 15, 20 and 40 kg/ha recorded a significant reduction in percent plant mortality compare to standard checks (phorate (10G) @ 25 kg/ha and imidacloprid (200SL) @ 500 ml/ha) and untreated check during both cropping seasons. The lowest (8.23 and 10.27) percent plant mortality was recorded in imidacloprid (0.3G) @ 40 kg/ha during both the cropping seasons. It was however, at par with its lower doses @ 15 and 20 kg/ha. Imidacloprid (0.3 G) @ 10 kg/ha recorded the percent plant mortality up to 17.97 and 15.73 during 2011 and 2012, respectively. A significantly higher yield was recorded under all the treatments doses over untreated check during both the years. Among the treatments a highest yield (1 810 and 1 830 kg/ha) of dry pod was recorded in imidacloprid (0.3G) @ 40 kg/ha during both the cropping seasons. It was however at par with its lower doses, i.e. imidacloprid 0.3G @ 15 and 20 kg/ha. Imidacloprid (0.3G) @ 20 kg/ha exhibited maximum net return of Rupees 64 078 ha. Hence, imidacloprid 0.3 G at 20 kg/ha may be recommended for the management of H. consanguinea on groundnut cultivated in sandy loam soil of Haryana.